May - Lasky, Kathryn (Lasky, Kathryn. Daughters of the sea, 2011)
In 1899 on an island off the coast of Maine, fifteen-year-old May learns why she has always felt different from the other girls in her small town, but must keep hidden that she is a mermaid or risk attracting the attention of a dangerous hunter, and losing a boy for whom she cares.